Atomic-scale analysis on a rubber-brass adhesive interface using scanning transmission electron microscopy. (16th January 2023) - Miyata, Tomohiro; Shimizu, Katsunori; Sato, Yohei K.; Jinnai, Hiroshi
Abstract: At rubber-brass (Cu–Zn alloy) adhesive interfaces, Cux S (x = 0.5–2) layers form during vulcanization, indicating that the mechanical and chemical interactions between rubber and brass strongly depend on the morphologies and chemical compositions of Cux S layers. In this study, an ultrathin cross-sectional sample of a rubber-brass adhesive interface was successfully prepared and observed by scanning transmission electron microscopy (STEM) with atomic resolution. It was revealed that the Cux S layer mainly consisted of two phases: hexagonal Cu2 S ( h -Cu2 S) and orthorhombic CuS ( o -CuS). While the h -Cu2 S grains had spherical shapes on the brass side of the Cux S layer, o -CuS grains with elongated shapes were on the rubber side of the layer. Moreover, the crystal faces of the Cux S grains and the areal densities of the sulfur atoms in the crystal faces, which would lead to the chemical conditions of the adhesive interface, were identified. This study provides indispensable information to clarify the adhesive mechanisms between rubber and brass. Graphical abstract: Image 1 Highlights: A rubber-brass adhesive interface was observed using atomic-resolution STEM. Nanocrystals of hexagonal Cu2 S and orthorhombic CuS composed the interfacial layer. The crystal structures determined the grain shapes and interfacial morphologies. Crystal faces of Cux S grains in contact with the rubber compound were identified. The areal densities of sulfur atoms in the crystal faces were estimated.